Solomon's knot : how law can end the poverty of nations - Cooter, Robert (Kauffman Foundation series on innovation and entrepreneurship., 2012)
Sustained growth depends on innovation, whether it's cutting-edge software from Silicon Valley, an improved assembly line in Sichuan, or a new export market for Swaziland's leather. Developing a new idea requires money, which poses a problem of trust. The innovator must trust the investor with his idea and the investor must trust the innovator with her money. Robert Cooter and Hans-Bernd Schäfer call this the "double trust dilemma of development." Nowhere is this problem more acute than in poorer nations, where the failure to solve it results in stagnant economies. In Solomon's Knot, Cooter and Schäfer propose a legal theory of economic growth that details how effective property, contract, and business laws help to unite capital and ideas. They also demonstrate why ineffective private and business laws are the root cause of the poverty of nations in today's world. Without the legal institutions that allow innovation and entrepreneurship to thrive, other attempts to spur economic growth are destined to fail.